Development of "Shasiko Bags" from the Utilization of Sasirangan Fabric Waste as Practical Teaching Material in Textile Experiment Subjects and Decorative Design In Vocational Schools - Yuyun Khoriatin; Imami Arum Tri Rahayu (Journal of Science and Education (JSE), 2026)
This research aims to develop shasiko bags from the use of sasirangan fabric waste as teaching materials for vocational school students. This research is development research (RnD) that uses the ADDIE (Analisys, Design, Development, Implementation, and Evaluation) development model. However, this study was only carried out until the development stage due to the limited research time. At the analysis stage, it was found that a lot of sasirangan fabric waste had not been utilized optimally. The design stage produces product designs in the form of designs on printed paper. The results of expert validation show that the products developed are in the category of being very valid, both in terms of appearance and function. The findings of this study also contribute to the development of similar learning products. Further research is recommended to test the effectiveness of bag products on various materials in vocational schools.